pth moment exponential stability of stochastic fuzzy Cohen–Grossberg neural networks with discrete and distributed delays - Xu, Changjin; Li, Peiluan (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, stochastic fuzzy Cohen–Grossberg neural networks with discrete and distributed delays are investigated. By using Lyapunov function and the Ito differential formula, some sufficient conditions for the pth moment exponential stability of such stochastic fuzzy Cohen–Grossberg neural networks with discrete and distributed delays are established. An example is given to illustrate the feasibility of our main theoretical findings. Finally, the paper ends with a brief conclusion. Methodology and achieved results is to be presented.
Keywords: stochastic fuzzy Cohen–Grossberg neural networks; global pth moment exponential stability; discrete delays; distributed delay; Ito differential formula